Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 8259 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Corbicula fluminea (O.F.Müller, 1774)", "HasGeospatialIssue is false", "HasCoordinate is true" ] } The dataset includes 8259 records from 54 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0009022-160623103540712/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences